The Influence Of School Operational Assistance (Bos) Funds On The Optimization Of The Teaching And Learning Process At Pisangsambo 1 Tirtajaya State Primary School - Nunung, Ai; Dian Candra Fatihah; Euis Hernawati; Sonia Azizah Putri Solihah (SAMPURASUN, 2023)
This study aims to determine how much influence School Operational Assistance Funds have on Optimizing the Teaching and Learning Process and Cultural Heritage Can Be Saved at SDN Pisangsambo 1 Tirtajaya. The research method used is descriptive verification method by collecting data through field studies, questionnaires and literature study. In this research, the sample used was 32 teachers at SDN Pisangsambo 1 Tirtajaya. Based on the research results, it was obtained a correlation coefficient of 0.430 which stated that the influence of BOS funds on optimizing the teaching and learning process of Cultural Heritage Can Be Saved at SDN Pisangsambo 1 is categorized as moderate because it is in the range of 0.40-0.599. The results of the t hypothesis test show that the amount of t count to t table is 2.612 > t table 1.697 which means that there is an influence between BOS funds on optimizing the teaching and learning process by saving culture. Based on the results of the calculation of the coefficient of determination, an R square of 18.5% is obtained, which means that the optimization of the teaching and learning process at SDN Pisangsambo 1 is influenced by BOS funds of 18.5%. The obstacles that occurred at SDN Pisangsambo 1 Tirtajaya were the lack of optimal communication received and the lack of knowledge of the recipients of BOS funds, which hampered the process of managing BOS funds implemented in the school. The suggested solution for schools is to increase effective two-way communication between the school and teachers and to disseminate knowledge about the management of BOS funds more intensely so that it can run well and systematically. Providing appropriate BOS can motivate schools to improve the quality of school education.